PENGATURAN ANGGARAN PENDAPATAN DAN BELANJA NEGARA MELALUI PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG - Moh Rizaldi (Departement of Constitutional Law IAIN Tulungagung, 2021)
It is still a matter of debate whether the State Revenue and Expenditure Budget can be regulated by government regulation in lieu of law. For the pros, this arrangement can be done because it is based on the suitability of types, hierarchies and content material. Meanwhile, for those who are contra, this arrangement violates the principle of people